Moving toward High Performance Organization of the Office of NBTC through Thailand Quality Award : TQA - Wanichwasin, Somsak (Journal of Digital Communications, 2019)
This article aims to study conceptual framework of modern management tools to which it can be suitable deployed for the NBTC Office. The study focuses on qualitative analysis of Thailand Quality Award- TQA and used documentary research. Its results reveal that TQA, as a modern management tools, is widely recognized in a great number of countries. Those in private sector that awarded TQA are accepted as highly performance corporations. More importantly, TQA also plays a virtual role as a basis of performance appraisal system like PMQA and SEPA for government and government-related agencies, as well as state-enterprises accordingly. TQA is a guideline for seeking excellence in all aspects. In the end, it can help the organization achieve its vision and support the1st 20-year Thailand National Strategic Plan, through enhancing the government’s and government-related agencies management system. TQA help improve productivity and re-shape work systems within the organization to better functions. It is really challenging for the NBTC Office to take part in playing a significant role in moving the country towards digital Thailand. In addition, TQA is flexible enough to work well with other managerial tools. The core principle of TQA lies on an organization assessment in all aspects in order to find out whether the organization performs well as compared to the benchmark. What indicators present? Whether or not any things should be changed? How to do? And when implementing the tools, success factors should be concerned, also structure of the operational team, and assessment method to be deployed.